2018
DOI: 10.3390/molecules23112760
|View full text |Cite
|
Sign up to set email alerts
|

VE-Albumin Core-Shell Nanoparticles for Paclitaxel Delivery to Treat MDR Breast Cancer

Abstract: Multi-drug resistance (MDR) presents a serious problem in cancer chemotherapy. In this study, Vitamin E (VE)-Albumin core-shell nanoparticles were developed for paclitaxel (PTX) delivery to improve the chemotherapy efficacy in an MDR breast cancer model. The PTX-loaded VE-Albumin core-shell nanoparticles (PTX-VE NPs) had small particle sizes (about 100 nm), high drug entrapment efficiency (95.7%) and loading capacity (12.5%), and showed sustained release profiles, in vitro. Docking studies indicated that the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Alloy and heterojunction nanomaterials have received tremendous interest in nanoscience and nanotechnology due to the synergistic effect. [174][175][176][177][178][179][180] The design of a large number of nanomaterials with heterojunctions in the interface between two different crystalline regions is indeed playing a vital role in the advanced materials for high-performance device applications. [181][182][183][184][185][186][187][188] Benefiting from the facilely controlled morphology and thickness-dependent bandgap, the synthetic approaches and versatile applications of Bi-based alloys and heterojunctions have quickly launched up in recent years.…”
Section: Bi-based Alloys and Heterojunctionsmentioning
confidence: 99%
“…Alloy and heterojunction nanomaterials have received tremendous interest in nanoscience and nanotechnology due to the synergistic effect. [174][175][176][177][178][179][180] The design of a large number of nanomaterials with heterojunctions in the interface between two different crystalline regions is indeed playing a vital role in the advanced materials for high-performance device applications. [181][182][183][184][185][186][187][188] Benefiting from the facilely controlled morphology and thickness-dependent bandgap, the synthetic approaches and versatile applications of Bi-based alloys and heterojunctions have quickly launched up in recent years.…”
Section: Bi-based Alloys and Heterojunctionsmentioning
confidence: 99%
“…Moreover, safety concerns about non-biodegradable inorganic materials such as oxidative stress and lung inflammation, impaired efficiency of anti-tumor ability are asked by researchers. Answer to these questions, many approaches have been developed 1416. Polyethylene glycol (PEG) modification of NPs has been made to enhance the longevity in blood circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel (PTX), also known as Taxol, is used as a drug in clinical treatment against different cancers. However, as it causes different side effects, Tang et al [69] suggested vitamin E (VE)-albumin core-shell nanoparticles (NPs) to improve the efficacy of PTX in BC models. They also investigated the cytotoxicity with in vitro approaches on MCF-7 BC cell lines.…”
Section: Targetmentioning
confidence: 99%
“…They also investigated the cytotoxicity with in vitro approaches on MCF-7 BC cell lines. Docking studies were performed to analyze the interaction between PTX or VE and BSA, and the results demonstrated a strong receptor-ligand interaction and PTX-VE NPs exhibited better cytotoxic effects than PTX NPs [69].…”
Section: Targetmentioning
confidence: 99%